COMPARATIVE ANALYSIS OF ACCELERATION ALTERNATIVES FOR THE DRAINAGE CHANNEL PROJECT ON XYZ STREET USINGTHE TIME-COST TRADE-OFF (TCTO) METHOD - Prasetiyo W., Arif; Oetomo, Wateno; Wulandari, Esti (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2023)
In response to the increasing occurrence of rain, the city government is actively striving to mitigate urban flooding by enhancing the drainage system. Collaboration with contracted construction firms is central to this endeavor, although it is not without its challenges, including community opposition driven by concerns over potential disruptions and limited financial resources among contractors. This study adopts the Critical Path Method (CPM) and Microsoft Project software, supplemented with the Time Cost Trade Off (TCTO) method to expedite project completion, emphasizing a comprehensive evaluation that encompasses both time and financial aspects. Notably, the analysis identifies the most feasible acceleration opportunity within the excavation of ordinary soil for construction, with original plans indicating a cost of Rp. 60,818,919 over a 40-day period. Three alternatives are considered: (1) overtime labor, incurring Rp. 65,520,000, with a 34-day duration; (2) increased workforce, incurring Rp. 68,000,000, with a 34-day duration; and (3) introducing a new addendum for the replacement of manual excavation with heavy machinery, incurring Rp. 37,440,000, with a 16-day duration. In conclusion, this study provides a comprehensive strategy for accelerating the urban drainage project, considering the critical path, time-cost trade-offs, and cost-benefit factors, highlighting the significance of selecting the most cost-effective alternative while addressing community concerns and resource limitations in flood risk mitigation efforts.